2017
DOI: 10.14814/phy2.13481
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of age‐related penile microvascular hemodynamic impairment using laser speckle contrast imaging: possible role of increased fibrogenesis

Abstract: Current technology for penile hemodynamic evaluations in small animals is invasive and has limitations. We evaluated a novel laser speckle contrast imaging (LSCI) technique to determine age‐related changes in penile microvascular perfusion (PMP) and tested the role of cavernosal muscle (CC) fibrosis mediated by Wnt‐TGF β1 signaling pathways in a mouse model. Ten young (2–3 months) and old (24–28 months) wild‐type C57BL6 male mice were subjected to PMP measured using a LSCI system. Penile blood flow (PBF, peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Penile MVP was assessed by the PeriCam PSI system (Perimed AB, Järfälla, Sweden). This laser speckle Doppler imaging technique quantifies penile MVP and displays a real-time image using arbitrary perfusion units (AU) [ 9 ]. The rats were prepared by using Nair hair remover in the pelvic region and were placed on a custom-made rat-restrainer lying supine, with their pelvis/penis positioned under the PeriCam ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Penile MVP was assessed by the PeriCam PSI system (Perimed AB, Järfälla, Sweden). This laser speckle Doppler imaging technique quantifies penile MVP and displays a real-time image using arbitrary perfusion units (AU) [ 9 ]. The rats were prepared by using Nair hair remover in the pelvic region and were placed on a custom-made rat-restrainer lying supine, with their pelvis/penis positioned under the PeriCam ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Microcirculation refers to the smallest arteries (less than ~150 µm in diameter), arterioles, capillaries, and venules. Reports suggest that penile microvascular dysfunction is an important contributor to ED severity and an underlying mechanism linking ED to cardiovascular disease [ 9 10 ]. In addition, a pre-clinical study from Department of Urology, VA San Diego Health Care System has revealed that increased penile fibrosis has been shown to impair penile microvascular perfusion (MVP) [ 9 ] measured using a novel laser speckle contrast imaging (LSCI) system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation